N-dimensional Lomb Scargle Periodogram analysis of traveling ionospheric disturbances using ionosonde data - Hughes, Joe; Collett, Ian; Newheart, Anastasia; Kelly, Ryan; Wilson, Walter Junk; Obenberger, Ken; Landry, Russell; Colman, Jonah; Malins, Joe (Frontiers in Astronomy and Space Sciences, 2024)
There is a multitude of wave-like phenomena in Earth’s ionosphere and thermosphere such as acoustic waves, gravity waves, planetary waves, tides, and Traveling Ionospheric Disturbances (TIDs) which are the ionospheric manifestation of atmospheric waves. These phenomena are often difficult to study since measurements are typically irregular in time and space due to geographic constraints for deploying ground instruments and the natural orbital motion of satellites. This frequently precludes Fourier methods such as the Fast Fourier Transform (FFT) from being used. The Lomb-Scargle Periodogram (LSP) provides FFT-like analysis when measurements are irregular. To our knowledge, all prior use of the LSP in space science has been one-dimensional. This paper uses a N-Dimensional extension of the LSP (ND LSP) to study traveling ionospheric disturbances in four dimensions on a quiescent day near solar minimum. We use an exquisite dataset consisting of 12 ionosondes over Australia on June 29, 2019. The ND LSP resolves the full 3-dimensional wave vector as well as the period for many discrete TIDs. To the degree possible, we validate our findings from ionosonde data processed with the ND LSP by using an FFT-based method on line-of-sight TEC data from the same period and find similar wavelengths and periods for the large TIDs. We show that TIDs occur preferentially near 70o elevation and could be missed or mischaracterized if using TEC data in the thin-shell approximation.